Arsenic removal from acidic solutions with biogenic ferric precipitates - Ahoranta, Sarita H.; Kokko, Marika E.; Papirio, Stefano; Ozkaya, Bestamin; Puhakka, Jaakko A. (ELSEVIER SCIENCE BV, 2016)
Treatment of acidic solution containing 5 g/L of Fe(II) and 10 mg/L of As(III) was studied in a system consisting of a biological fluidized-bed reactor (FBR) for iron oxidation, and a gravity settler for iron precipitation and separation of the ferric precipitates. At pH 3.0 and FBR retention time of 5.7 h, 96-98% of the added Fe(II) precipitated (99.1% of which was jarosite). The highest iron oxidation and precipitation rates were 1070 and 28 mg/L/h, respectively, and were achieved at pH 3.0. Subsequently, the effect of pH on arsenic removal through sorption and/or co-precipitation was examined by gradually decreasing solution pH from 3.0 to 1.6 (feed pH). At pH 3.0, 2.4 and 1.6, the highest arsenic removal efficiencies obtained were 99.5%, 80.1% and 7.1%, respectively. As the system had ferric precipitates in excess, decreased arsenic removal was likely due to reduced co-precipitation at pH< 2.4. As(III) was partially oxidized to As(V) in the system. In shake flask experiments, As(V) sorbed onto jarosite better than As(III). Moreover, the sorption capacity of biogenic jarosite was significantly higher than that of synthetic jarosite. The developed bioprocess simultaneously and efficiently removes iron and arsenic from acidic solutions, indicating potential for mining wastewater treatment. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Arsenic removal; Iron; pH control; Fluidized-bed reactor; Biogenic jarosite; ACIDITHIOBACILLUS-FERROOXIDANS; MINE WATER; SCHWERTMANNITE; JAROSITE; BIOOXIDATION; COPPER; LEPTOSPIRILLUM; GROUNDWATER; BIOREACTOR; Engineering; Environmental Sciences & Ecology